1987
DOI: 10.1002/bit.260290510
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of milk coagulation: IV. The kinetics of the gel‐firming process

Abstract: A mechanistic kinetic model of gel firmness development during milk gel formation is presented. The model correctly accounts for the influence of enzymatic kappa-casein hydrolysis on the rate of firmness development in renneted milk gels. The model used is based on two first-order reactions occurring in series. The first reaction is enzymatically controlled and corresponds to the formation of gel crosslink sites by kappa-casein hydrolysis. The second reaction is nonenzymatic and corresponds to the process of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…* Throughout this paper the term "kinetics of milk coagulation" will be used to refer to the (observed) rate at which visible precipitates (flocs) or gels of casein protein form in fluid milk. coagulation time, t,, and the amount of enzyme used in the reaction, Eo, was a constant for a given milk sample at a given pH and temperature, i.e., t,Eo = c (1) It was observed that the value of the constant, c, depended on the pH, temperature, and source and composition of the particular milk sample. This simple model has often been used as a basis for comparing the activities of enzymes and for standardizing enzyme solution~.~~ ' Unfortunately, there are many experimental conditions under which eq.…”
Section: Introductionmentioning
confidence: 98%
“…* Throughout this paper the term "kinetics of milk coagulation" will be used to refer to the (observed) rate at which visible precipitates (flocs) or gels of casein protein form in fluid milk. coagulation time, t,, and the amount of enzyme used in the reaction, Eo, was a constant for a given milk sample at a given pH and temperature, i.e., t,Eo = c (1) It was observed that the value of the constant, c, depended on the pH, temperature, and source and composition of the particular milk sample. This simple model has often been used as a basis for comparing the activities of enzymes and for standardizing enzyme solution~.~~ ' Unfortunately, there are many experimental conditions under which eq.…”
Section: Introductionmentioning
confidence: 98%
“…The step of the p--CN aggregation starts when 60-85% of the surface -CN has been proteolyzed by the enzymatic action exerted by the chymosin, the enzymatic rennet component that is able to act specifically on -CN at the time the enzymatic hydrolysis was produced in our working conditions [37]. Therefore, this step is usually overlapped with the end of the first one.…”
Section: Aggregation Of ä-Cn Particles By Enzymatic Actionmentioning
confidence: 98%
“…The standard Hansen's liquid rennet was a gift of COTAR S.A. (Argentine, Rosario) with a milk-clotting activity of 0.03 RU, where 1 RU is the required activity for rennet in 100 s 10 mL of dried milk suspension reconstituted in 10 mM CaCl 2 at no adjusted pH (approximately 6.4) and in IDF standard 110A:1987 specified conditions. Under conditions of rennet excess, the p--CN aggregation kinetics can be studied by estimating the initial rate of doublet formation, as proposed by Smoluchowski for Brownian aggregation [37], from the measurement ofˇchanges as a function of time. Three millilitre samples of 0.04% of -CN samples in 10 mM Tris-HCl, 10 mM CaCl 2 , at pH 6.4 were poured into spectrophotometer cuvettes in a jacketed cuvette holder maintained at 35 • C by water circulation, in a diode array Spekol 1200 spectrophotometer.…”
Section: Aggregation Of ä-Cn Particles By Enzymatic Actionmentioning
confidence: 99%
“…Rheology, on the other hand, provides an alternative approach to studying structure formation. Using a strain within the linear viscoelastic regime (LVR), the structure development during a process can be monitored by a rheometer, and a wealth of information has been reported on rheological data to illustrate the kinetics of network formation [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%